The effects of stress on avoidance in rodents: An unresolved matter - López-Moraga, Alba; Beckers, Tom; Luyten, Laura (Frontiers in Behavioral Neuroscience, 2022)
In the face of a possible threat, a range of physiological (e.g., increased heart rate) and behavioral (e.g., avoidance or escape) responses are recruited. Here, we will focus on avoidance, in its persistent form one of the core symptoms of anxiety disorders and obsessive-compulsive disorder. The initial goal of fear and avoidance responses is to increase survival, but if they become persistent or overgeneralize, they can disrupt normal daily functioning, and ultimately even result in anxiety-related disorders. Relatedly, acute stress responses promote adaptation and survival, while chronic stress has been found to aggravate pathophysiology. Thus, stress might trigger the transition from adaptive to maladaptive responses, e.g., from goal-directed to persistent avoidance. Animal models are prime tools to unravel if and how stress influences avoidance. This is typically done by performing stress inductions prior to the assessment of (passive or active) avoidance behavior. Despite its clinical relevance, the current literature on this topic is fragmented, and an overall conclusion is lacking. In this Review, we first recapitulate the state of the art regarding stress and active as well as passive avoidance procedures. We then summarize the behavioral effects of acute and chronic stress on active and passive avoidance, and discuss the main neurobiological findings of the field. Finally, we highlight possible reasons for the largely contradictory findings in the literature and we propose strategies to further unravel the effect of stress on avoidance behavior. A deeper understanding of this currently unresolved matter may provide further insights in the etiology and treatment of anxiety-related disorders.